1988
DOI: 10.1099/0022-1317-69-11-2755
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of the Semliki Forest Virus Mutant ts22 for the Foetal Mouse: Induction of Skeletal and Skin Defects

Abstract: SUMMARYThe maximum proportion of skeletal and/or skin defects induced by the Semliki Forest virus (SFV) mutant ts22 in the 17-day-old foetal mouse occurred following infection of the mother at day 10 of pregnancy. The skeletal defects were detected using a combination of Alcian blue staining for cartilage and Alizarin red staining for bone.Using immunogold-silver staining with anti-SFV IgG and in situ hybridization with a cDNA probe to SFV non-structural sequences, we have shown that mesenchymal cells in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The A7 ts22 mutant is teratogenic, inducing skeletal, skin, and neural tube defects in developing fetuses (Mabruk et al, 1988(Mabruk et al, , 1989. This is of interest given the teratogenic effects of the related rubella virus.…”
Section: Neuroinvasion Cns Tropism and Age-related Virulencementioning
confidence: 98%
“…The A7 ts22 mutant is teratogenic, inducing skeletal, skin, and neural tube defects in developing fetuses (Mabruk et al, 1988(Mabruk et al, , 1989. This is of interest given the teratogenic effects of the related rubella virus.…”
Section: Neuroinvasion Cns Tropism and Age-related Virulencementioning
confidence: 98%
“…e central nervous system contained only small amounts of viral antigen and nucleic acid. It is proposed that the skeletal and skin defects induced in mouse foetuses by ts22 infection result from the tropism of the virus for mesenchymal cells involved in the development of such tissue [98]. Damage to the neural tube, including open neural tube defects, was detected in foetuses following infection of the mother at days 8 and 10 of pregnancy with both A7 and ts22.…”
Section: Foetal Infectionmentioning
confidence: 99%
“…This was based on the method described previously for fetal tissue sections (Mabruk et al, 1988), using the methods of Holgate et al (1983) andSpringall et al (1984). For IGSS with anti-GC serum, treatment with Tween 80 was omitted.…”
Section: Immunogold-silver Stainingmentioning
confidence: 99%
“…For IGSS with anti-GC serum, treatment with Tween 80 was omitted. The anti-SFV antiserum, together with the corresponding pre-immune serum, was the polyclonal rabbit IgG described previously (Mabruk et al, 1988), and used .at a dilution of 1/80. Western blotting showed that this antiserum contained antibodies to all the viral structural proteins and some nonstructural proteins.…”
Section: Immunogold-silver Stainingmentioning
confidence: 99%